Get real 2 : (McMillan, 2001)
"Get Real!" is a four-level course in American English that has been developed for learners of English in East Asia. It has been specifically created to meet the needs of East Asian students in terms of level, pace, approach, cultural relevance and design. Key features are: familiarizing students with the English they are most likely to hear, by exposing them to a variety of regional and international accents; introduction to new language in culturally appropriate contexts through a wide range of topic